Evaluation of Communication Strategies in Addressing Narcotics Issues in the Region Through Optimizing the Role of the Regional National Narcotics Agency (BNN) - Prasetya Yoga SANTOSO; Ridzki Rinanto SIGIT; Tintin TINTIN; Novalia Agung Wardjito ARDHOYO (International Journal of Environmental, Sustainability and Social Science, 2025)
Indonesia faces a serious risk of narcotics abuse. The National Narcotics Agency of Indonesia (BNN RI) has recorded hundreds of areas vulnerable to narcotics distribution, including regions that are very difficult for authorities to access. The varying levels of threat across different areas demand a strategic approach that is locally adapted yet still effective. Nevertheless, an evaluation regarding the role of regional BNN is necessary. This is important considering Indonesia's 2045 Gold Vision targets, Asta Cita point 4, the Grand Design of Population Development (DBPK), and the Grand Design of Family Development (GDPK). Based on the above description, there is an issue that requires the evaluation of communication strategies in addressing narcotics problems in the regions through optimizing the role of regional BNN. The evaluation of communication strategies, which is the topic of this research, uses the Lasswell formula. Data was obtained through FGD activities and the collection of various relevant secondary data. Based on the research analysis, communication strategies are not yet optimal in the components of the communicator, message clarity, appropriate media selection, in-depth understanding of the audience, and a systematic feedback system. The weaknesses of these components are related to local political and financial dynamics. With the presence of Regional Regulations, it serves as an umbrella for eradicating narcotics through the spirit of collaboration between Ministries and Agencies